Inflammasome and toll-like receptor signaling in human monocytes after successful cardiopulmonary resuscitation. Issue 1 (December 2016) - Asmussen, Alexander; Fink, Katrin; Busch, Hans-Jörg; Helbing, Thomas; Bourgeois, Natascha; Bode, Christoph; Grundmann, Sebastian
Abstract Background Whole body ischemia-reperfusion injury (IRI) after cardiopulmonary resuscitation (CPR) induces a generalized inflammatory response which contributes to the development of post-cardiac arrest syndrome (PCAS). Recently, pattern recognition receptors (PRRs), such as toll-like receptors (TLRs) and inflammasomes, have been shown to mediate the inflammatory response in IRI. In this study we investigated monocyte PRR signaling and function in PCAS. Methods Blood samples were drawn in the first 12 hours, and at 24 and 48 hours following return of spontaneous circulation in 51 survivors after cardiac arrest. Monocyte mRNA levels of TLR2, TLR4, interleukin-1 receptor-associated kinase (IRAK)3, IRAK4, NLR family pyrin domain containing (NLRP)1, NLRP3, AIM2, PYCARD, CASP1, and IL1B were determined by real-time quantitative PCR. Ex vivo cytokine production in response to stimulation with TLR ligands Pam3 CSK4 and lipopolysaccharide (LPS) was assessed in both whole blood and monocyte culture assays. Ex vivo cytokine production of peripheral blood mononuclear cells (PBMCs) from a healthy volunteer in response to stimulation with patients' sera with or without LPS was assessed. The results were compared to 19 hemodynamically stable patients with coronary artery disease. Results Monocyte TLR2, TLR4, IRAK3, IRAK4, NLRP3, PYCARD and IL1B were initially upregulated in patients following cardiac arrest. The NLRP1 and AIM2 inflammasomes were downregulated in resuscitated patients. There was a significant positive correlation between TLR2, TLR4, IRAK3 and IRAK4 expression and the degree of ischemia as assessed by serum lactate levels and the time until return of spontaneous circulation. Nonsurvivors at 30 days had significantly lower mRNA levels of TLR2, IRAK3, IRAK4, NLRP3 and CASP1 in the late phase following cardiac arrest. We observed reduced proinflammatory cytokine release in response to both TLR2 and TLR4 activation in whole blood and monocyte culture assays in patients after CPR. Sera from resuscitated patients attenuated the inflammatory response in cultured PBMCs after co-stimulation with LPS. Conclusions Successful resuscitation from cardiac arrest results in changes in monocyte pattern recognition receptor signaling pathways, which may contribute to the post-cardiac arrest syndrome. Trial registration The trial was registered in the German Clinical Trials Register (DRKS00009684 ) on 27/11/2015.